Analysis Of President Joko Widodo's Government Performance Using A Philosophical Approach Of Public Administration - Naufal Noor Rochman (IHSA Institute, 2022)
This paper has the intention to know how public philosophy affects public administration in building governance and better state relations with society in the future. For this reason, an analysis of President Joko Widodo's Government Performance from Year 2019 to 2024 is conducted with a philosophical approach to the axiology of public administration science. The result of the discussion is that public philosophy will improve public administration quality through public inter-dependency, public learning, and public language, which create dynamic public space and encourage public involvement and participation so that the public understands the complexity of public policy. Furthermore, increasing public understanding encourages state relations with society to be better in supporting the success of governments in building state governance in the future.